Preferential Appointment of Science and Technology - Fathi Salem Abouzakhar (Journal of Pure & Applied Sciences, 2018)
Modern life is characterized by the acceleration of the progress of science and technology, and we do not see the need for competing with such an acceleration as much as we must create the environment for the progress of life in science and technology, and able to tame and employ optimal recruitment. With the infrastructure of the educational and research environment in Libya, we can absorb science and technology in a way that enables us to prioritize its effective employment on the land of Libya and commensurate with its capabilities as well as the capabilities of the actors on its soil. The researcher considers that the priorities of the employment of science and technology may take two aspects: a former aspect of employment in general and related to the required infrastructure, including vision, mission and objectives, to enable and settle science and technology properly in the institutions of basic and higher education and vocational and technical centers as well as research. The other side is related to the optimal employment and we can call it prioritization of employment as available from raw materials, data and possibilities that are necessary and that will yield early results that are feasible and capable of creating development, prosperity and civilization. The use of technology itself takes two directions: a trend that raises the level of science collection, technical and research groundwork, and a trend that selects the best choices to create real development that rises to the level of well-being. Therefore, the paper will discuss samples of the experiences of some countries that have been able to employ the technology optimally in their countries, with limited technological capabilities, and to use them in selecting some suitable applications for Libya. The measurement will be a real attempt to identify some of the applications through which we can call it the optimal choice of technology in Libya.